Kneading to die ebook - Mugavero, Liz (A Pawsitively Organic Mystery., 2013)
"Like the goodies Stan makes for her Maine coon kitty Nutty, Kneading To Die is a treat . . . A fun and frisky whodunit, with plenty of lively pet action." —Clea Simon, author of Cats Can't Shoot Maybe the best thing that ever happened to Kristan "Stan" Connor was losing her high-stress public relations job. Now there's plenty of time to spend in her sleepy new Connecticut town working on her dream: baking healthy, organic pet treats! Before long the neighborhood dogs are escaping their yards to show up at Stan's doorstep, begging for the kinds of special homemade treats her Maine coon cat Nutty loves so much. And Stan's pet-loving neighbors are thrilled with the new organic options available to their furry family members. But not everyone loves Stan and her newfangled organic ways . . . It seems Carole Morganwick, the town vet, is from the old school of pet care. But when Stan swallows her pride and brings a very unwilling Nutty in for a checkup, she not only finds Carole dead under a pile of kibble...but also learns that she's in the dog house as the prime suspect! Finding the real killer and clearing her name will require some seriously surreptitious sniffing around . . . and hopefully, curiosity won't kill this innocent cat . . . "The characters ring true and the plot and narration are seamless." — Mystery Scene "Animal lovers and foodies will hunger for more of this yummy new series." —Avery Aames, author of The Long Quiche Goodbye Includes Gourmet Pet Food Recipes!